(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This paper investigates the critical role of local governments in managing cross border collaboration and regional cooperation for sustainable development. As global challeng es such as climate change, resource depletion, and environmental degradation increasingly transcend national borders, local governments are uniquely positioned to address these issues through regional cooperation. The study uses a qualitative research meth odology, analyzing multiple case studies from various regions where local governments have been actively engaged in cross border initiatives. The research explores strategies employed by local governments, such as joint resource management, policy alignmen t, and shared governance, to foster sustainable development across borders. Key findings indicate that successful collaboration is dependent on the establishment of strong communication channels, trust building efforts, and formal governance structures tha t integrate regional interests. However, significant challenges remain, such as political differences, varying legal frameworks, and financial constraints, which hinder the effectiveness of these initiatives. Despite these barriers, the research highlights the potential of local governments, when supported by regional organizations, to drive sustainable development. The study concludes by suggesting that further research should focus on developing innovative solutions to overcome these obstacles and strengt hen cross border collaboration for sustainable development.